What does queer theory teach us about intersectionality? - Duong, Kevin (Politics & Gender, 2012)
“What does queer theory teach us about x ?” ask Berlant and Warner (1995). “As difficult as it would be to spell out programmatic content for an answer, this simple question still has the power to wrench frames” (p. 348). This challenge comes from an early essay published to circumvent queer theory's appropriation. Its power “to wrench frames” is what I am posing to intersectional research, not only to reflect on what intersectionality has allowed feminists to accomplish but also to identify some existing shortcomings in the scope and domain of its employment. Because there is little disputing intersectionality's theoretical contribution to feminist research in the past decades—one scholar calls it “the most important theoretical contribution that women's studies . . . has made so far” (McCall 2005, 1771)—it is important for us to take stock of the sorts of political problems that intersectional scholarship has addressed and the ones to which it has often been inattentive.
Keywords: approches et analyses; cours; cycles supérieurs; fem9000; intersectionnalité; queer; ressource en ligne